Arts Based Education Relevance in Seratwedhatama by K.G.P.A.A Mangkunegaran IV in Nusantara - Setyo Pambudi; Sigit Tri Utomo; Nur Alfi Muanayah (International Journal of Social Learning (IJSL), 2020)
This research is intended to find out the values of Islamic Education in the Wedhatama book written by KGPAA Mangkunegaran IV which is very relevant today. This research is a type of literature study research by looking for theoretical references that are relevant to the cases or problems found. Data collection techniques using documentation, observation and study literature Tajusalatin Fiber. The data that has been obtained are then analyzed using descriptive analysis methods. Descriptive analysis method is carried out by describing the facts which are then followed by analysis, not only describing, but also providing adequate understanding and explanation. To understand the full meaning of Wedhatama, it is necessary to begin with knowing the outline of the contents of the Pupuh tembang pangkur, which is an opening of the teachings that in general to walk towards "Penembah" must begin with "ngungkuraken angkara", which is to throw away the nature and attitude of the haunted, greedy , greed, wrath, cunning, envy, envy and so on. Character or virtue, as one of the basic teachings in religion, in order to be implemented in society, the king needs to be supported by all his apparatus. Meanwhile, a king who is aware of his mission and duty to uphold goodness, must need religious guidance, as seen in the expression "religion ageme aji".